Pregnant women in vehicles: Driving habits, position and risk of injury. (April 2016) - Auriault, F.; Brandt, C.; Chopin, A.; Gadegbeku, B.; Ndiaye, A.; Balzing, M.-P.; Thollon, L.; Behr, M.
Highlights: Measurements of 15 pregnant volunteers in driving position were performed. The distance between the abdomen and the steering wheel changes from 16.8 ± 5.4 cm at 6 months to 11.9 ± 4.1 cm at 9 months of pregnancy. A questionnaire on general driving habits was proposed to 135 pregnant women. Even in accidents with minor maternal injury, the fetus may sustain major injury. Abstract: This study proposed to broadly examine vehicle use by pregnant women in order to improve realism of accident simulations involving these particular occupants. Three research pathways were developed: the first consisted in a questionnaire survey examining the driving habits of 135 pregnant women, the second obtained measurements of 15 pregnant women driving position in their own vehicle from the 6th to the 9th month of pregnancy by measuring distances between body parts and vehicle parts, and the third examined car accidents involving pregnant occupants. Results obtained indicate that between 90% and 100% of pregnant women wore their seat belts whatever their stage of pregnancy, although nearly one third of subjects considered the seat belt was dangerous for their unborn child. The measurements obtained also showed that the position of the pregnant woman in her vehicle, in relation to the various elements of the passenger compartment, changed significantly during pregnancy. In the studied accidents, no correlation was found between the conditions of the accident and the resulting fetal injury. Results reveal that pregnant women do not modify significantly the seat setting as a function of pregnancy stage. Only the distance between maternal abdomen and steering wheel change significantly, from 16 cm to 12 cm at 6 and 9 month respectively. Pregnant women are mainly drivers before 8 months of pregnancy, passengers after that. Car use frequency falls down rapidly from 6 to 9 months of pregnancy. Real crashes investigations indicate a low rate of casualties, i.e. 342 car accidents involving pregnant women for a period of 9 years in an approximately 1.7 million inhabitants area. No specific injury was found as a function of stage of pregnancy.